2012
DOI: 10.3109/0142159x.2012.656751
|View full text |Cite
|
Sign up to set email alerts
|

Supporting traditional PBL with online discussion forums: A study from Qassim Medical School

Abstract: Blending e-learning with conventional PBL may help overcome student-perceived shortcomings of conventional PBL and improve the learning experience, making learning more interactive and interesting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…The findings indicate that students at Saudi universities are satisfied with using ODFs (see Table 6). This finding supports the work of Alamro and Schofield (2012) and Altaf (2013), who revealed similar findings in the same context. It is also in line with the findings of Shana (2009), who found that students are satisfied with using ODFs alongside traditional learning in another context.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The findings indicate that students at Saudi universities are satisfied with using ODFs (see Table 6). This finding supports the work of Alamro and Schofield (2012) and Altaf (2013), who revealed similar findings in the same context. It is also in line with the findings of Shana (2009), who found that students are satisfied with using ODFs alongside traditional learning in another context.…”
Section: Discussionsupporting
confidence: 82%
“…A high level of life commitments or engaging in the labour market may make those students with these particular demographics more satisfied with using ODFs than others where such obligations are the responsibility of the students. This finding is likely to be attributable to the flexibility in time and location when using ODFs (Al-Ismaiel, 2013;Alamro & Schofield, 2012;Bye, Smith, & Rallis, 2009;Cheung, Hew, & Ling Ng, 2008;Ismail, Mahmood, & Babiker, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Within the scope of the electronically implemented PBL applications in medical education, there are examples indicating that sharing learning material supporting classical face-to-face PBLs, online discussion platforms following the PBL sessions, clinical reasoning applications in which students are able to participate in at different times individually or in groups and multimedia scenarios, virtual patients are integrated to PBL sessions [4,7,[9][10][11][12][13]. In Dokuz Eylul Faculty of Medicine model, all of the steps in the classical PBL format were electronically actualized by the students in synchronized e-PBL sessions.…”
Section: Resultsmentioning
confidence: 99%